Rare bird documentation form for Greater Scaup at Lake Manawa in 1981 - Bray, Tanyaet al; Kovanda, Sandraet al; Padelford, Babset al; Rose, B.J.et al (1981)
Rare bird documentation form for a Greater Scaup at Lake Manawa in Pottawattamie County, IA on October 20, 1981. Epson - sheet feed